(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Twenty six different maize cultivars were planted in a Completely Randomized Block Design (CRBD) at AKS University, Satna, in November 2021 during the Rabi season. Twelve quantitative traits were examined, and data was gathered and analyzed for variance, correlation coefficient, and path coefficient. The experimental design showed significant variations in all traits as a result of the treatments. The analysis of variance for the twenty six maize genotypes revealed a considerable amount of variability among the genotypes for all traits under study.